Predictive factors of arterial calcification severity in computed tomography angiography (CTA) lower limbs - Wahab, Norhazura Abdul (2018)
Background: The use of multi-detector row technology has resulted in shorter acquisition time, increased volume coverage, lower dose of contrast medium, and improved spatial resolution for assessing small arterial branches. However the accuracy of the computed tomography angiography (CTA) examination may be degraded by the presence of calcified plaque. The objective of this study is to evaluate the factors that contribute to the severity of arterial calcification in CT lower limbs. Methodology: A cross sectional study that conducted in Hospital Universiti Sains Malaysia. CT lower limbs with calcifications from January 2010 to May 2017 were selected for this study. Patients who were amputated, CT images with metallic stent, and those with inadequate clinical information were excluded from the study. The calcium score was analyzed using the standardized calcium score software that was used for coronary arteries. Calcium score was divided into low and high using normal distribution curve. Possible clinical factors that affect arterial calcification were studied such as peripheral arterial disease symptoms, history of acute coronary symptoms, cardiovascular disease, end stage renal disease, blood cholesterol level, smoker/non-smoker, treated for diabetes/hypertension and latest systolic blood pressure. Framingham Risk Score was calculated using General cardiovascular disease Risk Prediction calculator, from official website Framingham Heart Study. Results: A total of 51 patients was included in the study (n=51) with the mean age was 67. Majority of the participants were Malay (88.2%). The numbers of male and female participants were almost equal. Multivariate analysis showed that interrelated factors that affect log arterial calcium score included age, diabetes, peripheral arterial disease and low density lipoprotein (R2 =0.589, p<0.001 to 0.015). There weresignificant moderate correlation between Framingham Score and Agatston Score. (r=0.555, p=0.001). Conclusion: Age, diabetes mellitus, peripheral arterial disease and low density lipoprotein are the potential associated factors that can be used to screen for possibility of severe lower limb arterial calcifications. High Agatston score is associated with high Framingham risk score.